Eco-Friendly Fabrication of SnO2-Curcumin Nanoparticles via Pterocarpus marsupium Extract: Unveiling Potent Antimicrobial and Anticancer Applications - Albratty, Mohammed; Makeen, Hafiz A (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Curcumin-SnO2 Nanoparticles (NPs) are advanced materials that combine organic molecules and inorganic substances in a single nanoscale platform to create hybrids with unique and enhanced properties. The synergy between the two components often results in improved functionality, stability and efficacy. Objectives The current work was conducted on Curcumin-SnO2 NPs synthesized using an eco-friendly method with Pterocarpus marsupium extract and evaluated their antimicrobial and cytotoxic effects on MDA-MB-231 cancer cells. Materials and Methods The synthesized Curcumin-SnO2 NPs were characterized using various methods, including XRD, SEM, PL and UV-visible spectroscopy analyses. The antimicrobial property of Curcumin-SnO2 NPs was assessed by the disc diffusion method against various pathogens. The cytotoxicity of Curcumin-SnO2 NPs on MDA-MB-231 cancer cells was assessed by a WST-1 assay. Results Characterization of Curcumin-SnO2 NPs using X-ray Diffraction (XRD) revealed a tetragonal structure. Photoluminescence (PL) spectra ranging from 350 to 550 nm indicated the presence of tin and oxygen vacancies (surface defects). The Curcumin-SnO2 NPs exhibited higher antimicrobial activity against Bacillus megaterium, Klebsiella pneumoniae and Candida albicans than conventional antibiotics. The Curcumin-SnO2 NPs effectively inhibited the viability of breast cancer cells. Conclusion These findings suggest the potential use of Curcumin-SnO2 NPs in healthcare institutions to improve patient outcomes.
Keywords: Curcumin; Nanoparticles; Pterocarpus Marsupium; MDA-MB-231 cancer cells.